Green roofs for energy efficiency and GBI compliance: A case study of government buildings in East Coast Malaysia - Mohamad Firdaus, Mohamad Borhan; Shahnizan Imran, Mohd Nazri; Nur Farhayu, Ariffin (Springer, 2025)
The Green Building Index (GBI) is Malaysia’s system for measuring the sustainable of the building, focusing on energy efficiency, indoor air quality, site management, materials, and water use. Although green roofs are not a specific requirement in the GBI, but it support the goals by improving energy efficiency, air quality, and site sustainability. This study focuses on the use of green roofs in East Coast Malaysia, and it contribute to building sustainability and this study also examines the impact of Roof Thermal Transfer Value (RTTV) on electricity cost reduction. A survey was conducted with engineers and assistant engineers from government agencies, including the Public Works Department and Inland Revenue Board. The results showed that successful green roof implementation depends on structural strength, good waterproofing, proper drainage, and choosing plants that suit the tropical climate. Regular maintenance is also important to keep green roofs working well over time. While green roofs offer benefits like better air quality and cooler buildings, high installation and maintenance costs make them harder to adopt. This study highlights on green roofs can help achieve GBI goals and improve building sustainability if financial and technical challenges are addressed. Furthermore, lower RTTV reduces heat transfer, decreasing cooling demand and cutting electricity costs by up to 70%, improve thermal performance, enhancing sustainability and cost savings.